Selection of the colloid for priming of cardipulmonary bypass - V. Yarovenko (Ukrainian Journal of Cardiovascular Surgery, 2016)
The study included 72 patients after heart valve replacement. For priming cardiopulmonary bypass machine used solutions of the modified gelatin and hydroxyethyl starch (HES). Serum cytokine levels were determined by ELISA (IL 1?, IL 6, TNF ?, IL 10). We have obtained a reduction in the inflammatory response and increase anti inflammatory response in patients with HES.